How to fill the information gap: Open Access for the social sciences and humanities - Ernst, Elisabeth; Schulte, Judith; Töpfer, Marlen (Septentrio Conference Series, 2020)
Researchers not actively seeking information about Open Access and scholars who are not actively informed by their institutions might be concerned about publishing Open Access due to lack of information. Questions such as “Why is Open Access necessary and what do I gain?”, “What happens to my rights as an author?”, and “Why was I not told about this discount before I paid the full APC from my project fund?” might come up. This workshop is directed at representatives of research organizations and universities (e.g. Open Access offices, project coordinators, and interested researchers) on the topic of helping researchers finding answers to these questions and advocating for Open Access in the humanities and social sciences. The workshop seeks to discuss aspects that have been identified by participants priorly as most pressing to discuss. For any questions, please don’t hesitate contacting Elisabeth Ernst and Judith Schulte (communication@operas-eu.org) OPERAS is the European Research Infrastructure for open scholarly communication in the social sciences and humanities. Its Special Interest Group on “Advocacy” works on topics related to the communication and advocating of Open Access in the social sciences and humanities and of those disciplines.